The roots and routes of revenge: trajectories of harm across forensic and clinical domains - Gozna, Lynsey (2020)
The prevalence of revenge in serious crime means that forensic practitioners need to assess the potential for future acts and deliver tailored interventions to reduce risk. In applied forensic settings, research considering the motive of revenge and the first-person experiences of clients who commit such offences, is limited. This thesis investigated the roots and routes of revenge, trajectories of harm and the opportunities for early intervention and public protection. This primarily investigated the first-person perspectives and experiences of male mentally disordered offenders who had committed offences in response to real or perceived transgressions. The outcome of this study illustrated the influence of prior exposure to traumatic events on future trajectories of revenge. An applied model of revenge was developed to inform work with clinical and forensic clients, whether convicted of or identified as ‘at risk’ of revenge. Early trauma and adversity were considered in a client case study of a revenge-oriented female arsonist with a complex mental health presentation. The influence of early maladaptive schemas and relational dynamics were especially relevant to the interpretation of responses to perceived or real slights and acts of revenge. The influence of human-induced trauma (experienced, witnessed or perpetrated) on the development of subsequent psychopathology (post-traumatic stress and embitterment) and corresponding thoughts, fantasies and acts of harm formed the focus of the scoping review. This considered the role of revenge and associated acts of harm in displaced (refugees and asylum seekers) populations, civilians in post-war communities, veterans and combatants (including former child soldiers), genocide perpetrators and survivors, victims of crime and offenders. The assessment of ‘Propensity for Revenge’ (PfR) was considered in a psychometric critique which emphasised the challenges for practitioners working with offending and ‘at risk’ populations. The implications of these distinct but iterative research studies on revenge are discussed along with research and practice recommendations.